KEMAMPUAN MENYIMAK TEKS NEGOSIASI SISWA KELAS X SMK NEGERI 1 PENDALIAN IV KOTO - Cici Nurfauzianah Has; M. Nur Mustafa; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research entitled the ability to listen to the text of the negotiation of class X students of SMK Negeri 1 Pendalian IV Koto. The purpose of this study is to describe the ability to listen to the text of the negotiation of class X students of SMK Negeri 1 Pendalian IV Koto, and to describe the different ability of listening text of the negotiation of the students of class X SMK Negeri 1 Pendalian IV Koto between groups of sample and per sex of the sample. The data of this research is the result of the test of the ability to listen to the text of the negotiation of class X students of SMK Negeri 1 Pendalian IV Koto which is divided into 3 classes namely class X TKJ-1, class X TKJ-2 and class X Accounting and consists of 76 members of the population with a sample of 64 students. Result of research after doing testing by using chi square test of one sample get result χ2 count equal to 68,2, whereas χ2 79,1. The hypothesis of chi square test of one sample is Ho accepted when χ2 count <χ2 table. This means Ho accepted, meaning the ability to listen to the text ngeosiasi students class X SMK Negeri 1 Pendalian IV Koto relatively low. In addition, the authors also tested using chi squares of two samples, to determine whether or not the ability to listen to the text of the negotiation of students of class X SMK Negeri 1 Pendalian IV Koto between groups of sample and per sex of the sample. The result, after the test using chi square test of two samples, that is obtained price χ2 count 7,791 and price χ2 table amounted to 79.10. Chi squared is accepted if hypothesis χ2 count <χ2 table. Test results show Ho accepted, meaning there is no difference to the ability to listen to the text of the negotiation of students of class X SMK Negeri 1 Pendalian IV Koto between groups of samples and per sex of the sample.Keywords: ability, listening, negotiation text